Perioperative patient safety recommendations - SAFEST Consortium (2024)
Funding Information: This work was funded by the European Union Horizon Europe Framework Programme under grant agreement No. 101057825. No other funding sources were received for this study. The authors wish to thank Eulalia Grifol Clar (Head of the Medical Library, Hospital Universitario Fundaci\u00F3n Alcorc\u00F3n) and Noelia \u00C1lvarez D\u00EDaz (Head of the Medical Library, Hospital Universitario Ram\u00F3n y Cajal) for conducting a literature search and Azahara Rodr\u00EDguez-Luna for the initial development of the protocol of this study. Funding Information: This work was funded by the European Union Horizon Europe Framework Programme under grant agreement No. 101057825. No other funding sources were received for this study. Acknowledgements Publisher Copyright: © The Author(s) 2024.